A polarisation maintaining fibre Bragg grating interrogation system for multi- axis strain sensing - Ye, Chen-Chun; Staines, Stephen E.; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2002)
Fibre Bragg gratings (FBGs) written into polarisation maintaining (PM) fibres have been employed for multi-axis strain and temperature sensing. In this paper we report the development of a FBG interrogation system that is capable of detecting independently the two orthogonally polarised signals reflected from a PM FBG. The interrogation system imposes no limitation on the measurable strain range. This relaxes the requirements on the bandwidth of the grating spectrum, allowing the use of a shorter PM FBG (larger bandwidth) for sensing applications where a higher spatial resolution is required. In particular, this system is useful in the cases where the spectra of the reflected polarised signals are broadened or split, resulting from strain-induced structural changes of the PM fibre, or caused by the application of a non-uniform strain on the FBG.
Keywords: Fibre Bragg grating; Interrogation system; Multi-axis strain sensor; Polarisation maintaining